The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1111/j.1574-0862.2006.00164.x
|View full text |Cite
|
Sign up to set email alerts
|

Supply response in Ethiopia: accounting for technical inefficiency

Abstract: Few empirical studies of supply response using the profit function have accounted for technical inefficiency. Using farm-level panel data from Ethiopia, this study examines the effect of incorporating technical inefficiency in estimating the supply response of peasant farmers. Two systems of output supply and input demand equations are estimated and compared: the conventional model in which technical efficiency is assumed and another in which technical inefficiency is explicitly incorporated. The model with te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…For an extensive report on pro‐poor policies in Ethiopia and the role of agriculture, aid and agency in poverty reduction in the 1990s, see World Bank (2005). Detailed analysis of performance of agriculture during this period is found in Abrar et al (2004) and Abrar and Morrissey (2006).…”
mentioning
confidence: 99%
“…For an extensive report on pro‐poor policies in Ethiopia and the role of agriculture, aid and agency in poverty reduction in the 1990s, see World Bank (2005). Detailed analysis of performance of agriculture during this period is found in Abrar et al (2004) and Abrar and Morrissey (2006).…”
mentioning
confidence: 99%
“…(3) The effects of inefficiency as an explanatory variable on supply response using a profit function approach (Abrar and Morrissey 2006), and estimate and compare inefficiency from stochastic frontier analysis (SFA) with ordinary least square (OLS) during 1994 to 2004 (Bachewe, 2009). This paper covers a longer time (1994 -2009) than Bachewe (2009).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly in Africa, some efficiency studies used to raise policy debates on the performance of the agricultural sector (Abro et al, 2014; Abrar and Morrissey, 2006; Alene and Hassan, 2006; Arega, 2010; Croppenstedt and Demeke, 1997; Haji, 2007). Results have been mixed and inconsistent across different modelling approaches and prevailing agro-ecological conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have even reported conflicting results from the same data set. For instance, using Ethiopian Rural Household Survey data, different authors (see Abrar and Morrissey, 2006; Abro et al, 2014) estimated different levels of TE of Ethiopian farmers. There are also inconsistencies in the theoretical relationships between TE and its determinants.…”
Section: Introductionmentioning
confidence: 99%